D-dimer and mortality in COVID-19: a self-fulfilling prophecy or a pathophysiological clue? (Swiss Medical Weekly, 2020)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) as a global phenomenon has presented clinicians around the world with multiple challenges. Thromboembolic events are recognised complications of viral infection, but the diagnosis of an acute pulmonary thrombotic complication in the context of coronavirus disease 2019 (COVID-19) can be challenging because of the similarities of presentation, logistical considerations of diagnosis in a patient isolated for infection control reasons and the effects of cognitive errors in diagnostic reasoning. We present the case of a patient who was diagnosed with a pulmonary thrombotic complication during inpatient care for COVID-19. The haemostasis parameters we observed, including increased levels of von Willebrand factor and factor VIII, point towards a relevant involvement of endothelial cells in patients with severe COVID-19. We suggest that it is possible to hypothesise a spectrum of secondarily acquired, prothrombotic coagulopathy mediated by the endothelial interaction with SARS-CoV-2 as a cause of mortality in a subset of patients with a complicated clinical course of COVID-19. We support the recommendation of thromboembolic chemoprophylaxis for inpatients with COVID-19 as a very minimum in the absence of strict contraindications, while recognising that pulmonary thrombotic complications can occur under standard thromboprophylaxis. We suggest that higher, possibly therapeutic levels of anticoagulation might be mandatory for a further subset of patients with COVID-19 where a discrepant evolution of C-reactive protein and D-dimer is observed. Therapeutic levels of anticoagulation are obligatory where new evidence of a macrovascular thrombotic complication has been documented. More research to delineate the macro- and microvascular thrombotic complications of COVID-19, and the therapeutic implications for this patient group is required.